Download as pdf or txt
Download as pdf or txt
You are on page 1of 7

BOOLEAN ALGEBRA

Commutative Law
A.B=B.A A+B=B+A
Associative Law
(A.B).C=A.(B.C) (A+B)+C=A+(B+C)
Distributive Law
A.(B+C)=A.B+A.C
AND LAW
A.0=0 A.1=A A.A=A A.A'=0
OR LAW
A+0=A A+1=1 A+A=A A+A'=1
Involution law
A''=A
Demorgan's Law
(A.B)'=A'+B' (A+B)'=A'.B'
Absorption Law
X+XY=X X(X+Y)=X
Logic Gates
AND OR NOT NAND NOR XOR XNOR
A.B A+B A' (A.B)' (A+B)' A XORB AXNORB
Literal
A and A'
F(A,B) =>2NLiterals=4Literals A,A',B,B'[N-No of V'bles]
EX:F(A,B)=A+A'B (Minimum no of Literals)
F(A,B,C) =>6 Literals A,A',B,B',C,C'
SIMPLIFY:
1)XY+XY' = X(Y+Y') = X
2)(X+Y)(X+Y') = XX+XY'+XY+YY' = X(1+Y'+Y) = X
3)XYZ+X'Y+XYZ' = XY(Z+Z')+X'Y = Y(X+X') = Y
BOOLEAN FUNCTION
Variables - N 2N Possible Combinations based on
true(A) and complement(A') form.
Boolean Function can be expressed in
 Minimal Form F=X+Y'Z
Minimal Number of variables can exists.
 Canonical or Standard Form F=XYZ+X'Y'Z+X'Y'Z'
 All the variables must exist in all the terms either
in true or complement form.
 Each product term is called minterm.
 Each sum term is called Maxterm.
2N minterms(m) 0-Comp, 1-true
2N Maxterms(M) 0-true, 1-comp
X Y Z Minterm(Product) Maxterm(Sum)
0 0 0 X'Y'Z'(m0) X+Y+Z(M0)
0 0 1 X'Y'Z(m1) X+Y+Z'(M1)
0 1 0 X'YZ'(m2) X+Y'+Z(M2)
0 1 1 X'YZ (m3) X+Y'+Z'(M3)
1 0 0 XY'Z'(m4) X'+Y+Z(M4)
1 0 1 XY'Z (m5) X'+Y+Z'(M5)
1 1 0 XYZ' (m6) X'+Y'+Z(M6)
1 1 1 XYZ(m7) X'+Y'+Z'(M7)
Canonical or Standard Form
 Sum Of Product (SOP)
 Product Of Sum (POS)
SOP: F=X'Y'Z + XY'Z' + XY'Z + XYZ' + XYZ
POS: F=(X+Y=Z)(X+Y'+Z)(X+Y'+Z')
Express F=X+Y'Z using sum of minterms and product
of maxterms.
X Y Z F
0 0 0 0
0 0 1 1 F=X'Y'Z + XY'Z' + XY'Z + XYZ' + XYZ
0 1 0 0 F= (X+Y+Z) (X+Y'+Z) (X+Y'+Z')
0 1 1 0
1 0 0 1
1 0 1 1
1 1 0 1
1 1 1 1
Express the Boolean Function F=A+B’C as a sum of
minterms.
F=A+B'C
=A(B+B')(C+C')+(A+A')B'C
=ABC + ABC' + AB'C + AB'C' + AB'C + A'B'C
=Σ(m7, m6, m5, m4, m1)
F'= Σ(m0,m2,m3)
Express the Boolean Function F=xy+x’z as a product of
maxterms.
F=xy+x'z
=(xy+x')(xy+z)
=(x+x')(x'+y)(x+z)(y+z)
=(x'+y+zz')(x+yy'+z)(xx'+y+z)
=(x'+y+z)(x'+y+z')(x+y+z)(x+y'+z)(x+y+z)(x'+y+z)
=Π(M4, M5, M0, M2)
Given the function as defined in the truth table,
express F as sum of minterms and product of
maxterms and F' as sum of minterms and product of
maxterms.

F = x'y'z + x'yz + xy'z' = Σ(m1, m3, m4)


[sum of 1 - minterms]
F = (x+y+z) (x+y'+z) (x'+y+z') (x'+y'+z) (x'+y'+z') = Π(M0,
M2, M5, M6, M7)
[product of 0 - Maxterms]
F' = Σ(m0, m2, m5, m6, m7)
[sum of 0 - minterms]
F' = Π(M1, M3, M4)
[product of 1 - Maxterms]
Express F=(x+yz)' as sum of minterms.
F = (x+yz)' = x' (yz)'
= x' (y'+z')
= x'y' + x'z'
= x'y'(z+z') + x'(y+y')z'
= x'y'z + x'y'z' + x'yz' + x'y'z'
Remove the duplicates
= Σ(m0, m1, m2)

Convert F(A,B,C,D)=Σ(0,1,2,4,5,7) into POS.


F = ΠM(3, 6, 8, 9 ,10, 11, 12, 13, 14, 15)
F= (A+B+C'+D') (A+B'+C'+D) (A'+B+C+D) (A'+B+C+D')
(A'+B+C'+D) (A'+B+C'+D') (A'+B'+C+D) (A'+B'+C+D')
(A'+B'+C'+D) (A'+B'+C'+D')

You might also like